Measuring and assessing the impact of literacy, numeracy and computer skills on labor market outcomes in the Philippines - Llana, Ma. Christina Banaag (School of Economics, University of the Philippines Diliman, 2019)
Though literacy, numeracy, and computer skills are some of the human capital components that education aims to produce, formal education may not able to accurately reflect these skills. As an effect, traditional human capital models cannot fully capture labor market outcomes. Using data from the STEP Skills Measurement Household Survey conducted in the Philippines, we create interaction variables between literacy, numeracy, and computer skills, then run a simple OLS regression and logistic regression to estimate the effects of these skills on employment and earnings. Our findings show that the individual skill variables improve labor market outcomes more than the education variable does in the Philippines. Notable of the three is possessing high numeracy skill, which increases employment chances by 74 percent and earnings by 77 percent. As for the interaction terms, numeracy and computer skills are important for better employment chances while reading and computer skills are important for better earnings. Possessing high reading and high numeracy skill gives a .713 average probability of employment, while possessing high reading and medium or high computer skill, as well as possessing low or medium numeracy and medium computer skill, gives an average log earnings value of 4. The Heckman Selection Model eliminates bias in the log earnings model, where we find a 100 percent increase in earnings related to having medium reading skill and high numeracy skill. Possessing no reading skill is seen to decrease log earnings by nearly 5 percent. We find that low skill levels are rewarded in the Philippine labor market because majority of the jobs available do not require skilled workers. Consequently, these workers earn less than highly skilled Filipinos employed in top positions. However, high computer skill remains a consistent key in improved labor market outcomes. The government programs in the Philippines only aim to improve functional literacy, but now we have evidence that computer skill is also important, especially in 21st century skill acquisition. Thus, the inclusion of computer skill development in these programs could contribute to improved employment chances and earnings. In summary, the impact of literacy, numeracy, and computer skills on labor market outcomes has been explored in several other countries, but they have not been fully studied in the Philippines. We aim to fill that gap in this paper.